The Physical and Organoleptic Characteristics of Ground Rabbit Dendeng Fermented with Lactobacillus plantarum (Jurnal Ilmu dan Teknologi Hasil Ternak, 2020)
The purpose of this study was to determine the appropriate concentration of Lactobacillus plantarum and fermentation time used in fermented rabbit meat production as the main ingredient for producing ground dendeng. This study used a 4Ã—3 factorial randomized block design with three replications, which consisted of different L. plantarum concentrations (0%, 6%, 8%, and 10% v/w) and fermentation times(12 h, 18 h, and 24 h). Data were analyzed using two-way analysis of variance and continued with Duncan's multiple range tests. The concentration of L. plantarum and fermentation time had a highly significant effect (P <0.01) on the acidity. The L. plantarum concentration had a significant effect (P <0.05) while fermentation time had a highly significant effect (P <0.01) on pH. The concentration of L. plantarum and fermentation time had no effect on Aw, color, and texture. The concentration of L. plantarum had no effect on flavor, taste, and overall acceptance of dendeng. The fermentation time had a highly significant effect (P <0.01) on the flavor, and gave a significant effect (P <0.05) on the taste and overall acceptance of dendeng. In conclusion, the concentration of L. plantarum suitable for ground dendeng of fermented rabbit meat was 6% with 18 h fermentation time to produce the best physical and organoleptic quality and to obtain consumer acceptance.